Experimental Evaluation of Erosion of Gunmetal under Asymmetrical Shaped Sand Particle - Nuruzzaman, D. M.; Chowdhury, M. A.; Debnath, U. K.; Islam, M. M. (Hindawi Publishing Corporation, 2015)

(untitled)
The erosion characteristics of gunmetal have been evaluated practically at different operating conditions. Asymmetrical silica sand (SiO2) is taken into account as erodent within range of 300–600 μm. The impact velocity within 30–50 m/sec, impact angle 15–900, and stand off distance 15–25 mm are inspected as other relevant operating test conditions. The maximum level of erosion is obtained at impact angle 15° which indicates the ductile manner of the tested gunmetal. The higher the impact velocity, the higher the erosion rate as almost linear fashion is observed. Mass loss of gunmetal reduces with the increase of stand-off distance. A dimensional analysis, erosion efficiency (η), and relationship between friction and erosion indicate the prominent correlation. The test results are designated using Taguchi’s and ANOVA concept. ratio indicates that there are 1.72% deviations that are estimated between predicted and experimental results. To elaborately analyze the results, ANN and GMDH methods are mentioned. After erosion process of tested composite, the damage propagation on surfaces is examined using SEM for the confirmation of possible nature of wear behavior. The elemental composition of eroded test samples at varying percentage of gunmetal is analyzed by EDX analysis.